THEORETICAL AND METHODOLOGICAL ASPECTS TO IDENTIFY THE CULTURAL LANDSCAPE AND ECOTONAL ARCHITECTURE IN OBLATOS-HUENTITÁN CANYON, GUADALAJARA, MÉXICO - Massimi Malo, Carlos Xavier; Socio fundador y representante legal de la empresa Ingeniería y Arquitectura Jarex S.A. de C.V. Breve currículo (150-200 palabras) que mencione títulos académicos, vinculación institucional, premios y reconocimientos y últimas o más importantes publicaciones: (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2015)
The present article is a preview of the master´s degree thesis which study subject is the Oblatos-Huentitán canyon´s cultural landscape formed by the inclusion in its natural environment of constructions with typologies and characteristics that responses to the canyon´s ecotone, an transitional zone between Atemajac valley and Santiago river´s ecosystems in which besides the endemic vegetal and animal species that appears in each transitional area, it seems to be a certain kind of endemism in the manmade buildings. Assuming the UNESCO´s concepts of Cultural Landscape, besides the ecotonal´s concepts determined by authors like di Ventós, Holland, Hansen and di Castri, the methodological approach proposed bases in Grounded Theory taking the data of the canyon´s patrimonial value components to formulate different hypothesis that define the landscape´s characteristics and open horizons for the current definition of a particular Oblatos-Huentitán canyon´s architecture